(untitled) (Human Factors in Design, 2022)
In the search to define design artifacts, there are different views for the same artifact. In this article, the views of Sargent (1994) and Lobach (2001) are discussed, evaluating the presence of design in the Cyborg Beast prosthesis, an open source product for 3D printing. Articles from developers and users of the prosthesis were confronted with the perspectives of these authors, they were collected in Scopus and Google Scholar, with the descriptor “Cyborg Beast” until the year 2020. They fit in some aspects of Sargent (1994) and Lobach (2001), and it is concluded that artifacts can partially fit into design definitions, according to the developer or user perspective.